Physics Learning Using the Argument Driven Inquiry Model Integrated with Islamic Science to Improve the Argumentation Ability and Attitude Towards Physics of MA Students - Putri Rahmaddani; Azhar; Dedi Irawan (Jurnal Penelitian Pendidikan IPA, 2025)
Argumentation skills and positive attitudes toward physics are important aspects of 21st-century learning, but are still relatively low among Indonesian students. This study aims to improve these two aspects through the application of the Argument Driven Inquiry (ADI) learning model integrated with Islamic science. This study is a Classroom Action Research (CAR) conducted in two cycles on grade XI students of MAN 1 Pekanbaru with harmonic vibration material. The instruments used included attitude questionnaires, argumentation questions, observation sheets, and learning tools. Data were collected through observation and tests. The results showed a significant increase in teacher and student activities, attitudes toward physics, and students' argumentation skills. Learning activities developed from the Good to Very Good category. Attitudes toward physics increased from low to high and very high categories. Argumentation skills, which were initially classified as underdeveloped, became good to very good. These findings indicate that the ADI model integrated with Islamic science is effective in increasing student engagement and the quality of physics learning.